The Evaluation of Local and Systemic Reactions to Subcutaneous House Dust Mite Allergen Immunotherapy - Zuhal Karalı; Şükrü Çekiç; Yağmur Hazal Şadırvan; Yakup Canıtez; Nihat Sapan (Trends in Pediatrics)
Objective: Allergen-specific immunotherapy is an effective treatment method that enables the development of immunotolerance against allergens in allergic rhinitis, asthma, and venom allergy. This study investigated the local and systemic reactions during subcutaneous house dust mite allergen immunotherapy.